PENGARUH MODEL PEMBELAJARAN PROJECT-BASED FLIPPED CLASSROOM MELALUI PENDEKATAN PEMBELAJARAN MENDALAM BERBANTUAN MEDIA SMART APPS CREATOR (SAC) TERHADAP KEMAHIRAN MENULIS TEKS PANTUN SISWA KELAS VII SMP NEGERI 13 TANJUNGPINANG - Hanifashahira, Andrani; Elfitra, Legi; Testy Ariance Loren, Fabio; Leo Shanty, Isnaini; Pujiastuti, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the effect of a project-based flipped classroom learning model through a deep learning approach assisted by Smart Apps Creator media on the pantun text writing skills of seventh-grade students at SMP Negeri 13 Tanjungpinang. The study employed a quasi-experimental method with a quantitative approach. The research population encompassed all seventh-grade students at SMP Negeri 13 Tanjungpinang during the 2025/2026 academic year. A sample of 40 students was determined using a total sampling technique. Data were derived from pre-test and post-test scores of the students' pantun text writing proficiency. The results indicated that the implementation of the project-based flipped classroom learning model through a deep learning approach assisted by smart apps creator media significantly influenced the pantun text writing skills of the seventh-grade students. This finding is supported by the results of a nonparametric mann whitney u test at a 5% significance level, which yielded a Sig. (2-tailed) value or p-value of 0.027 < 0.05. Consequently, the alternative hypothesis (Ha) was accepted, and the null hypothesis (H0) was rejected. Based on these findings, it can be concluded that the use of a project-based flipped classroom learning model through a deep learning approach assisted by smart apps creator media exerts a significant effect on the pantun text writing skills of VII grade students.